2012
DOI: 10.1186/2046-2530-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia and aberrant cell signaling in epithelial ovarian cancer

Abstract: BackgroundOvarian cancer is the fourth leading cause of cancer-related deaths among women in Denmark, largely due to the advanced stage at diagnosis in most patients. Approximately 90% of ovarian cancers originate from the single-layered ovarian surface epithelium (OSE). Defects in the primary cilium, a solitary sensory organelle in most cells types including OSE, were recently implicated in tumorigenesis, mainly due to deregulation of ciliary signaling pathways such as Hedgehog (Hh) signaling. However, a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 88 publications
2
86
1
2
Order By: Relevance
“…In line with this result, analysis of PDGFRa mRNA and protein levels showed that PDGFRa is highly upregulated during serum deprivation in cultured cells, concomitantly with formation of the primary cilium (Lih et al 1996;Schneider et al 2005). Subsequent studies have confirmed cilia-specific localization of PDGFRa in a range of additional cell types, including rat astrocytes and neuroblasts (Danilov et al 2009), mouse heart ventricular cells (Gerhardt et al 2013), human embryonic stem cells (Awan et al 2010), ovarian surface epithelial cells (Egeberg et al 2012), and mouse osteoblasts (Noda et al 2016). Of note, in some ciliated cell types, such as rat oligodendrocytes (Falcon-Urrutia et al 2015) and mouse heart atrial cells (Gerhardt et al 2013), PDGFRa seems to be conspicuously absent from the organelle, whereas in retinal pigment epithelial (RPE) cells, which are commonly used in ciliary studies, PDGFRa seems hardly to be expressed at all (Lei et al 2011;Nielsen et al 2015).…”
Section: Primary Cilia and Regulation Of Pdgfraa Signalingsupporting
confidence: 48%
“…In line with this result, analysis of PDGFRa mRNA and protein levels showed that PDGFRa is highly upregulated during serum deprivation in cultured cells, concomitantly with formation of the primary cilium (Lih et al 1996;Schneider et al 2005). Subsequent studies have confirmed cilia-specific localization of PDGFRa in a range of additional cell types, including rat astrocytes and neuroblasts (Danilov et al 2009), mouse heart ventricular cells (Gerhardt et al 2013), human embryonic stem cells (Awan et al 2010), ovarian surface epithelial cells (Egeberg et al 2012), and mouse osteoblasts (Noda et al 2016). Of note, in some ciliated cell types, such as rat oligodendrocytes (Falcon-Urrutia et al 2015) and mouse heart atrial cells (Gerhardt et al 2013), PDGFRa seems to be conspicuously absent from the organelle, whereas in retinal pigment epithelial (RPE) cells, which are commonly used in ciliary studies, PDGFRa seems hardly to be expressed at all (Lei et al 2011;Nielsen et al 2015).…”
Section: Primary Cilia and Regulation Of Pdgfraa Signalingsupporting
confidence: 48%
“…Because so many different signaling systems are associated with primary cilia, 20,21,31,171,172,175,200,[213][214][215][216] we suggest that primary cilia may function as signaling hubs in the spatiotemporal crosstalking between diverse signaling networks during heart development. Future work should therefore focus on how primary cilia are involved in the integration and cross-talking between different signaling networks and how this may impact on different stages of heart development.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…170 Previous studies showed that PDGFRα specifically localizes to primary cilia in a number of cell types and tissues, including the heart, 22,[171][172][173][174][175][176] and that activation of the receptor and its downstream effectors, Mek1/2-Erk1/2-Rsk and Pi3K-Akt, is initiated in the cilium to regulate cell cycle control and directional cell migration in fibroblasts. 171,177,178 The recent finding that PDGFRα localizes to primary cilia in E11.5 mouse heart ventricles 22 (Fig.…”
Section: Cardiac Primary Cilia and Coordination Of Pdgf Signalingmentioning
confidence: 99%
“…Later on, nuclear presence of CHFR was explained via a short lysine-rich stretch (KKK) at amino acid residues 257-259 (Kwon et al, 2009). Egeberg et al, 2012 suggested a centrosome/primary cilium axis localization of CHFR. CHFR was also shown to localize to the mitotic spindle by an interaction with TCTP, a protein involved in microtubule stabilization and a-tubulin (Kim, 2011) Function Initially, CHFR was described to induce an early G2/M checkpoint in response to mitotic stress (Scolnick and Halozenetis, 2000).…”
Section: Localisationmentioning
confidence: 99%